Persister cells formation and expression of type II Toxin-Antitoxin system genes in Brucella melitensis (16M) and Brucella abortus (B19) - Fatemeh Amraei; Negar Narimisa; Behroz Sadeghi; Vahid Lohrasbi; Faramarz Masjedian Jazi (Iranian Society of Pathology, 2020)
Background & Objective: Persister cells are defined as a subpopulation of bacteria that are capable of reducing their metabolism and switching to dormancy in stress conditions. Persister cells formation has been attributed to numerous mechanisms, including stringent response and Toxin-Antitoxin (TA) systems. This study aimed to investigate the hypothetical role of TA systems in persister cells formation of Brucella strains by evaluating toxins of type II TA systems (RelE, Fic, Brn T, cogT) expression. Methods: Brucella strains treated with a lethal dose of gentamicin and ampicillin and to determine the number of surviving cells, bacterial colonies were counted at different time intervals. The role of TA systems in persister cell formation was then determined by toxin expression levels using qRT- PCR method. Result: Our results showed the viability of persister cells after 7 h. The results of relative qRT- PCR showed higher levels of toxin gene expression due to stress conditions, suggesting the possible role of TA systems in persister cells formation and antibiotics tolerance. Conclusion: The results of this study showed that considering the importance of persistence and the tolerance to antibiotics, further studies on persister cells formation and related genes such as the TA system genes in Brucella strains might help us to identify the precise mechanisms leading to persister cells formation.